2017
DOI: 10.1002/mc.22615
|View full text |Cite
|
Sign up to set email alerts
|

ABCF2, an Nrf2 target gene, contributes to cisplatin resistance in ovarian cancer cells

Abstract: Previously, we have demonstrated that NRF2 plays a key role in mediating cisplatin resistance in ovarian cancer. To further explore the mechanism underlying NRF2-dependent cisplatin resistance, we stably overexpressed or knocked down NRF2 in parental and cisplatin-resistant human ovarian cancer cells, respectively. These two pairs of stable cell lines were then subjected to microarray analysis, where we identified 18 putative NRF2 target genes. Among these genes, ABCF2, a cytosolic member of the ABC superfamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…Platinum-resistant tumor cells usually have a higher threshold for apoptosis induction, mostly due to the overexpression of anti-apoptotic proteins or the defect in mitochondrial signaling. Many factors contribute to these unwanted phenomenons, such as pro-survival signal pathways (Sun et al, 2016;Bao et al, 2017) [i.e., MAPK/ERK (Kong et al, 2015), PI3K/AKT pathway, NF-kB (Miow et al, 2015)], and tumor microenvironment (TME) and epigenetic regulation (Benard et al, 2014;Ramadoss et al, 2017). Researchers begin focusing on the critical role of non-coding RNA in diverse cellular processes; studies demonstrated that non-coding RNA broadly participated in proapoptotic/antiapoptotic proteins regulation and could work as therapeutic targets or predict markers Zarogoulidis et al, 2015).…”
Section: Apoptosismentioning
confidence: 99%
“…Platinum-resistant tumor cells usually have a higher threshold for apoptosis induction, mostly due to the overexpression of anti-apoptotic proteins or the defect in mitochondrial signaling. Many factors contribute to these unwanted phenomenons, such as pro-survival signal pathways (Sun et al, 2016;Bao et al, 2017) [i.e., MAPK/ERK (Kong et al, 2015), PI3K/AKT pathway, NF-kB (Miow et al, 2015)], and tumor microenvironment (TME) and epigenetic regulation (Benard et al, 2014;Ramadoss et al, 2017). Researchers begin focusing on the critical role of non-coding RNA in diverse cellular processes; studies demonstrated that non-coding RNA broadly participated in proapoptotic/antiapoptotic proteins regulation and could work as therapeutic targets or predict markers Zarogoulidis et al, 2015).…”
Section: Apoptosismentioning
confidence: 99%
“…Several mechanisms are proposed to account for the drug resistance phenotype and many of the genes reported to play roles in drug resistance are identified with a functional link with NRF2 [13] . In anticancer chemotherapy, NRF2 and NRF-dependent genes have been implicated in the cellular resistance to a wide range of anticancer agents (e.g., tamoxifen, Cisplatin, Oxaliplatin, Cisplatin, Doxorubicin, and Etoposide) and cancer types [18][19][20][21][22][23][24][25] . Likewise, the NRF2-centred system and signalling pathway is shown to modulate the action and effectiveness of certain receptor targeted therapies [26][27][28]224,231,232] and potentially promoting cancer resistance to such interventions as Trastuzumab, Pertuzumab, Erlotinib, Lapatinib, imatinib, Gefitinib, Afatinib and Osimertinib.…”
Section: Role Of Nrf2 In the Mechanism Of Action And Effectiveness Ofmentioning
confidence: 99%
“…We next examined potential drug resistance pathways, including genes encoding known drug transporters, solute transporters, cytochromes, oxidoreductases, and others (Table S2). Notably, intestinal stromal myofibroblasts had markedly enriched expression of a subset of ATP transporters that serve to efflux a broad range of substrates (Leslie et al, 2005;Vasiliou et al, 2009;Gottesman 2002;Bao et al, 2017) (Figure 4Ai). The most highly enriched and expressed of these were the well-known drug resistance genes, Abcc1 (Mrp1) and Abcb1b (Mdr1b) (Figure 4Aii).…”
Section: Intestinal Myofibroblasts Express Diverse Growth Factors Andmentioning
confidence: 99%